Infrastructure in Latin America - Calderón, César; Servén, Luis (2012)
An adequate supply of infrastructure services has long been viewed by both academics and policy makers as a key ingredient for economic development. Over the past quarter-century, the retrenchment of Latin America's public sector from its dominant position in the provision of infrastructure, and the opening up of these industries to private participation, have renewed the debate on the role of infrastructure in the region's development. The focus of this paper is three-fold. First, it documents, in a comparative cross-regional perspective, the trends in Latin America's infrastructure development, as reflected in the quantity and quality of infrastructure services and the universality of their access. Overall, this suggests the emergence of an infrastructure gap vis-a-vis other industrial and developing regions. Second, it provides an empirical assessment of the contribution of infrastructure development to growth across Latin America. Third, it examines the trends in the financing of infrastructure investment -- documenting the changing roles of the public and private sectors -- and analyzes how they have been shaped by macroeconomic policy constraints.